The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1603/0022-2585(2006)43[533:sopamr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Permethrin and Malathion Resistance in Human Head Lice Populations from Denmark

Abstract: Head lice, Pediculis capitis De Geer, populations were investigated for permethrin and malathion resistance after initial establishment of a discriminating dose of topical application bioassay with body lice, Pediculus humanus L. For both insecticides, approximately 2 times the lethal dose (LD)95 at 4 h was selected, 2 ng of permethrin and 100 ng of malathion per head louse, respectively. Head lice were collected from heads of infested children in Denmark at 33 primary schools, one kindergarten, and seven boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 22 publications
2
34
0
2
Order By: Relevance
“…Clinical and parasitological resistance to head lice was first observed in1994 [16]. Since then, head lice resistance has been often documented [6, 9, 21, 22]. Strategies for treating resistant lice include yearly rotation of available pediculicides, retrying the initial agent at a higher concentration or for a longer application time, and switching to a different product [3].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and parasitological resistance to head lice was first observed in1994 [16]. Since then, head lice resistance has been often documented [6, 9, 21, 22]. Strategies for treating resistant lice include yearly rotation of available pediculicides, retrying the initial agent at a higher concentration or for a longer application time, and switching to a different product [3].…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2003 reported a resistant kdr-like allele frequency ranging from 0.33 to 1.00 in California, Florida, and Texas [11]. Other studies have also reported variable frequencies: 0.07 in Japan [30], 0.44 in Wales, UK [31], 0.93 in France [32], 0.95 in Denmark [17], and 0.97 in Canada [33]. Indeed, the widespread use of pyrethroids may have been a key factor in the selection of homozygous resistant lice.…”
Section: Pyrethroidsmentioning
confidence: 99%
“…Resistance to malathion was first reported in France [39], and then in the UK [2], Australia [25], and Denmark [17]. The effectiveness of malathion in a single-blind, randomized study in the UK was poor, showing cure rates of only 17% (n = 30) [9].…”
Section: Malathionmentioning
confidence: 99%
“…Certainly, this is a factor contributing to the effect, partly because some people have become blasé about the efficacy of products, partly because they are trying to economize when faced with repeated need to treat, and partly through lack of skill. However, those same factors contributed to the development of acquired resistance to commonly used insecticides like permethrin and malathion and, when the warning signs of consumer dissatisfaction 25-30 years ago were not heeded, it resulted in complete loss of usefulness of the insecticides in most territories and regions within a little over a decade (Chosidow et al, 1994;Mumcuoglu et al, 1995;Rupeš et al, 1995;Burgess et al, 1995;Picollo et al, 1998;Pollack et al, 1999;Downs et al, 1999Downs et al, , 2002Hunter & Barker, 2003;Kristensen et al, 2006;Kasai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Head lice with acquired resistance to pyrethroid insecticides were identified more or less concurrently by several investigators from different countries in the early 1990s (Chosidow et al, 1994;Mumcuoglu et al, 1995;Rupeš et al, 1995;Burgess et al, 1995). Subsequently resistance and resistance mechanisms were identified in widely distributed territories (Picollo et al, 1998;Pollack et al, 1999;Hunter & Barker, 2003;Kasai et al, 2009) and were also found to affect other insecticides in addition to the pyrethroids (Downs et al, 1999(Downs et al, , 2002Kristensen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%